Ecotoxicology impact of silica-coated CdSe/ZnS quantum dots internalized in Chlamydomonas reinhardtii algal cells - Elzorkany, Heba Elsayed; Farghali, Mohamed A; Hassan, Mohamed A; El-Sayed, Kh; Canonico, Myriam; Konert, Grzegorz; Farroh, Khaled; Elshoky, Hisham A; Kaňa, Radek (The Science of the total environment, 2019)
The use of quantum dots (QD) in various medical and industrial applications may cause these nanoparticles to leak into waterways and subsequently enter the food chain. Therefore, if we intend to use QD, we must first know their potential environmental implications. In this work, cadmium selenide/zinc sulfide core/shell QD were synthesized, and then, biocompatible, water-dispersed QD were coated with silica (Si-QD). The QD were characterized by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM) combined with energy-dispersive X-ray spectroscopy (EDX), and UV-Vis absorption analysis, which revealed that these surface-engineered QD have a highly crystalline, homogeneous spherical shape measuring approximately 25 nm. The cytotoxicity of the nanoparticles in the green algae Chlamydomonas reinhardtii was studied by incubating the algae cells with Si-QD and determining the optical density of algal cell culture, cell counts, and cells sizes by microflow cytometry. These measurements indicated that Si-QD are biocompatible up to a concentration of 25 ng/ml. Finally, the cellular uptake of Si-QD into C. reinhardtii was monitored by confocal laser scanning microscopy (CLSM). In conclusion, our results reveal that surface-engineered Cd-QD can penetrate the cells of aquatic organisms, which ensures a serious impact on the food chain and consequently the environment. On the other hand, the results also highlight a new potential method for bioremediation of Cd-QD by green algae, especially C. reinhardtii.
Keywords: Sulfides; Selenium Compounds; Ecotoxicity; sulfidy; Nanocrystals; kovové nanočástice; sloučeniny zinku; sloučeniny selenu; Chlamydomonas reinhardtii; Zinc Compounds; Internalization of nanomaterials; Cadmium Compounds; Confocal microscopy; Quantum Dots; Bioremediation; sloučeniny kadmia; kvantové tečky; Metal Nanoparticles; Photosynthetic organisms